Sustainable Campus Wastewater Treatment using Anaerobic Baffled Reactor Systems - Anna Nisful Laili; Fahir Hassan; Cigdem Oz Yasar; Farida Rahmawati; Syifaa Azkia Azka; Rhenata Chriskeowny Telaumbanua; Anie Yulistyorini (Universitas Trisakti, 2026)
Aim: This study aims to investigate the efficiency of the Anaerobic Baffled Reactor (ABR) system in domestic wastewater treatment at the Graha Rectorate of the State University of Malang (UM), part of the UM Green Campus program. Methodology and results: The study was conducted by installing a laboratory-scale ABR system and investigating its performance in reducing pollutant concentrations. Sampling was carried out at the inlet and outlet ports, and the system was run for Hydraulic Retention Time (HRT) of 24 hours. The samples were analyzed for chemical oxygen demand (COD), biological oxygen demand (BOD), total suspended solids (TSS), Total Coliform (TC), pH, dissolved oxygen (DO), and temperature. The results showed that the ABR system with a flowrate of 1.408 m³/day and a reactor volume of 1.901 m³, consisting of 9 compartments, was able to reduce TSS and COD concentrations to meet the quality standards of Permen LHK No. 68/2016. Statistical tests showed significant reductions in COD, BOD, and TSS parameters. The removal efficiency of each parameter is TSS (91.33%), COD (40.44%), BOD (32.14%), and TC (51.18%). Conclusion, significance, and impact study: This study demonstrated that ABR is effective in treating campus wastewater, but further design optimisation or hybridisation with another system is still required. A combination of additional treatments is recommended to ensure compliance with regulatory standards and support the achievement of Sustainable Development Goals (SDG 6 and SDG 11), particularly in the areas of clean water and sanitation, as well as sustainable cities.